Does Consumer Like the Coffee? A Study of Product Quality of a Local Business Ground Roasted Coffee in North Sumatera - Wiyono, Sulistyodewi Nur; Utami, Hesty Nurul; Kamarulzaman, Nitty Hirawaty (International Journal of Social Science and Business, 2024)
Producers are required to provide quality products according to quality standards and consumer needs. Quality is one factor that consumers consider when buying a product. The coffee processing industry is rapidly growing because of the high demand for this product. "The X Coffee" is one of the ground coffee processing industries that applies quality control in its production process. Nevertheless, defects were still found in their products. This study aimed to identify the consumers' perception of the quality of ground-roasted coffee products. The research design used was a case study. Data were analysed using descriptive statistics. The results showed that consumer perceptions of coffee's price, colour, taste, and size were good and fit consumers' expectations. The most chosen attributes according to consumers' needs are product aroma and the least amount of coffee powder size. Improvements would be suggested related to the size of the coffee grounds for being too coarse to make them acceptable. Consumers perceived the packaging information as incomplete so more product information could be added to the package. The coffee beans tasted too bitter, which could reduce the roasting level. The priority improvement is to change the size of the coffee grind to a smoother one because it will affect the taste and convenience when consumed.